Myrmecobius fasciatus (Dasyuromorphia: Myrmecobiidae) - Cooper, Christine (American Society of Mammalogists, 2011)
Myrmecobius fasciatus Waterhouse, 1836, is a small to medium-sized dasyuromorph marsupial known as thenumbat. M. fasciatus is unusual among marsupials in that it is diurnal and feeds exclusively on termites, and it has a numberof characteristic adaptations associated with this specialized niche. M. fasciatus has at least 8 postcanine teeth in the lowerjaw; the dentition is variable between individuals and even between the 2 sides of the jaw of the same individual. Althoughwidespread throughout southern Australia at the time of European settlement, M. fasciatus is currently restricted to 2naturally occurring populations in the southwestern portion of Western Australia, and some additional populations within itshistoric range resulting from successful reintroductions. It is currently listed as ‘‘Endangered.’’